Etos Kerja, Budaya Organisasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT Galatta Lestarindo Sungai Lansek - Aziza Bella Ferari; Juarsa Badri (Jurnal Publikasi Ilmu Manajemen, 2023)
This study aims to examine the effect of work ethic, organizational culture and work environment on employee performance at PT Galatta lestarindo Sungai Lansek. This type of research is quantitative, where the research process emphasizes objective measurement of results using statistical analysis. The population in this study were all employees of 81 people. The sampling technique used is total sampling where total sampling is a sampling technique when all members of the population are sampled, while the number of samples is 81 people obtained from all employees. The type of data used in this research is quantitative and qualitative data. While the data sources are primary and secondary data sources. Data collection techniques using observation, questionnaires and literature study. by using test instrument test, (validity test and reliability test), classic assumption test (normality test, multicollinearity test and heteroscedasticity test) then multiple linear regression and hypothesis testing with the help of the SPSS application. Where multiple linear regression produces Y = 10,714 + 0.175 (X1) + 0.298 (X2) + 0.332 (X3) and the first hypothesis test shows that the t-count value is greater than t-table (2.048 > 1.99085) with a significantly smaller value of the alpha value (0.044 <0.05). This shows that H1 is accepted, which means that work ethic has a positive effect on employee performance. And the second hypothesis test shows that the t-count value is greater than t-table (3.041 > 1.99085) with a significantly smaller value than the alpha value (0.003 <0.05). This shows that H2 is accepted, which means that organizational culture has a positive effect on employee performance. And the third hypothesis test shows that the t-count value is greater than t-table (2.480 > 1.99085) with a significantly smaller value than the alpha value (0.015 <0.05).The results of the study show that work ethic has a positive and significant effect on employee performance. Organizational culture has a positive and significant effect on employee performance and the work environment has a positive and significant effect on employee performance.